Molécules chirales : stéréochimie et propriétés - Collet, André (Savoirs actuels., 2006)
"Chiral molecules" is a work which is extremely diversified. It deals with fundamental principles and the applications of chirality in chemistry. This book is intended for researchers, teachers, and students who are interested in chirality which is a common occurrence that is often overlooked.